Guided Internet-based versus face-to-face clinical care in the management of tinnitus: study protocol for a multi-centre randomised controlled trial - Beukes, Eldre W.; Baguley, David; Allen, Peter M.; Manchaiah, Vinaya; Andersson, Gerhard (BioMed Central, 2017)
Background